Designing anti-reflection coatings for optical surface - M. Meheretu, Getnet; E. Gebremeskel, Sitotaw (International Journal of Physical Research, 2019)
In this paper, we have analyzed the optical properties of single and double layer antireflection coatings with the help of influential characteristics matrix formulation method in the visible electromagnetic spectrum. We have studied deeply for the glass coated with MgF_2 as a single layer coating and the spectrum analysis of double layer coatings of glass with〖 MgF〗_2-Al_2 O_3. With the aid of the algebraic mathematics and MatLab program, we have developed antireflection coating designs which leads to an enhancement of material’s ability for transmission spectrum through it. According to the result we have obtained, it clearly seen that the maximum transmission power for single layer and double layer coatings are about 97.2% which occurs at wavelength of 450 nm and 100% occurs at 324 nm, respectively. It is also observed that the minimum value recorded in transmission spectra for double layer antireflection coating is 99.83% at a wavelength of 418 nm (for normal incidence) and 400 nm (for θ=60° angle of incident). In broadly speaking, our fundamental work shows double layer antireflection coating is more convenient and feasible than single layer antireflection coating.